2014
DOI: 10.1002/biot.201300445
|View full text |Cite
|
Sign up to set email alerts
|

Advances in metabolic engineering of yeastSaccharomyces cerevisiaefor production of chemicals

Abstract: Yeast Saccharomyces cerevisiae is an important industrial host for production of enzymes, pharmaceutical and nutraceutical ingredients and recently also commodity chemicals and biofuels. Here, we review the advances in modeling and synthetic biology tools and how these tools can speed up the development of yeast cell factories. We also present an overview of metabolic engineering strategies for developing yeast strains for production of polymer monomers: lactic, succinic, and cis,cis-muconic acids. S. cerevisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
166
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(167 citation statements)
references
References 74 publications
0
166
0
1
Order By: Relevance
“…Yeasts, and in particular S. cerevisiae, are widely used as a cell factory for production of various chemicals (83). However, all known TAL enzymes of fungal origin also have at least a partial PAL activity.…”
Section: Resultsmentioning
confidence: 99%
“…Yeasts, and in particular S. cerevisiae, are widely used as a cell factory for production of various chemicals (83). However, all known TAL enzymes of fungal origin also have at least a partial PAL activity.…”
Section: Resultsmentioning
confidence: 99%
“…The strategies for metabolic engineering to increase productivity have been commonly focused on improvement of the downstream synthesis pathway of the target chemicals as well as repression of the competitive pathways that form by-products (16)(17)(18). In addition, enhancement of upstream central carbon metabolism, i.e., uptake and metabolism of carbon sources, should be important so as to supply the precursor metabolites and coenzymes more efficiently.…”
mentioning
confidence: 99%
“…Recent advances in metabolic engineering of S. cerevisiae have shown that systems and synthetic biology tools are advanced and readily available nowadays, allowing rational construction of capable production strains (Li & Borodina, 2014, Fletcher et al, 2015. Through combination of metabolic modelling and genetic engineering S. cerevisiae can be analysed and tailored in silico as well as in vivo , Borodina & Nielsen, 2014. This allows even very complex natural product biosynthetic pathways to be reconstructed in this organism (Galanie et al, 2015, Kayser & Averesch, 2015.…”
Section: Yeast In Biotechnologymentioning
confidence: 99%